Why do children hospitalised with pneumonia not receive antibiotics in primary care?. Issue 1 (18th November 2011) - Grant, CC; Harnden, A; Mant, D; Emery, D; Coster, G
Abstract : Background: Although antibiotics are recommended for the primary care management of community-acquired pneumonia, a recent UK study reported that most children admitted to hospital had not received antibiotics. Objective: To describe primary care antibiotic use for children subsequently hospitalised with community-acquired pneumonia. Design/methods: A case series of 280 children <5 years old hospitalised with pneumonia in Auckland, New Zealand. Pneumonia was defined as an acute illness with cough or respiratory distress, the presence of tachypnoea or indrawing and an abnormal chest radiograph. Receipt of antibiotics was determined by parental report and medical record review. Results: Fewer than half (108, 39%) of the children had received an antibiotic before hospital admission. For 60 children (21%) there had been no opportunity to prescribe because the illness evolved rapidly, resulting in early hospital admission. For the remaining 112 children (40%) an opportunity to receive antibiotics was missed. The parent failed to obtain the antibiotic prescribed for 23 children (21% of 112), but in 24 children (21%) pneumonia was diagnosed but no antibiotic prescribed and in a further 28 children (25%) the diagnosis was not made despite parental report of symptoms suggesting pneumonia. Missed opportunities to prescribe were not associated with increased overall severity of symptoms at hospital presentation but were associated with an increased risk of: focal chest radiological abnormalities (rate ratio (RR)=2.14; 95% CI 1.49 to 2.83), peripheral leucocytosis >15×10 9 /l (RR=2.29; 95% CI 1.61 to 2.98) and bacteraemia (RR=6.68, 95% CI 1.08 to 58.44). Conclusions: Young children with community-acquired pneumonia may not receive an antibiotic before hospital admission because the illness evolves rapidly or the prescribed medicine is not given by parents. However, missed opportunities for appropriate antibiotic prescribing by health professionals in primary care appear to be common.